Genome-wide identification and phenotypic characterization of seizure-associated copy number variations in 741,075 individuals - TÜRKDOĞAN, DİLŞAD (My University, 2023)
Copy number variants (CNV) are established risk factors for neurodevelopmental disorders with seizures or epilepsy. With the hypothesis that seizure disorders share genetic risk factors, we pooled CNV data from 10,590 individuals with seizure disorders, 16,109 individuals with clinically validated epilepsy, and 492,324 population controls and identified 25 genome-wide significant loci, 22 of which are novel for seizure disorders, such as deletions at 1p36.33, 1q44, 2p21-p16.3, 3q29, 8p23.3-p23.2, 9p24.3, 10q26.3, 15q11.2, 15q12-q13.1, 16p12.2, 17q21.31, duplications at 2q13, 9q34.3, 16p13.3, 17q12, 19p13.3, 20q13.33, and reciprocal CNVs at 16p11.2, and 22q11.21. Using genetic data from additional 248,751 individuals with 23 neuropsychiatric phenotypes, we explored the pleiotropy of these 25 loci. Finally, in a subset of individuals with epilepsy and detailed clinical data available, we performed phenome-wide association analyses between individual CNVs and clinical annotations categorized through the Human Phenotype Ontology (HPO). For six CNVs, we identified 19 significant associations with specific HPO terms and generated, for all CNVs, phenotype signatures across 17 clinical categories relevant for epileptologists. This is the most comprehensive investigation of CNVs in epilepsy and related seizure disorders, with potential implications for clinical practice.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Fizik; Astronomi ve Astrofizik; Kimya; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Physics; Astronomy and Astrophysics; Chemistry; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); CHEMISTRY; SPACE SCIENCE; MOLECULAR BIOLOGY & GENETICS; ASTRONOMY & ASTROPHYSICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; Genel Kimya; Fizik Bilimleri; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Genel Fizik ve Astronomi; General Chemistry; Physical Sciences; General Biochemistry, Genetics and Molecular Biology; General Physics and Astronomy